The vanishing neighbor : the transformation of American community - Dunkelman, Marc J. (New York, NY : W.W. Norton & Company, Inc., 2014)
"Identifies [what the author sees as] an epochal shift in the structure of American life--a shift unnoticed by many. Routines that once put doctors and lawyers in touch with grocers and plumbers--interactions that encouraged debate and cultivated compromise--have changed dramatically since the postwar era. Both technology and the new routines of everyday life connect tight-knit circles and expand the breadth of our social landscapes, but they've sapped the commonplace, incidental interactions that for centuries have built local communities and fostered healthy debate. The disappearance of these once-central relationships ... lies at the root of America's economic woes, political gridlock and decline of the American dream."--Jacket.
Introduction: From one Queen City to the next -- Rumblings : The warning ; The third wave ; The Chinatown bus effect ; The big climb ; Conformity comes full circle -- The missing rings : A brief history of American community ; Bands, villages, and tribes ; The search for affirmation ; The missing rings ; Exit Tocqueville ; And now for something completely different -- America explained : Valuable inefficiency ; The roots of deliberation ; The giant sucking sound ; The marshmallow test -- Conclusion: The crisis of American exceptionalism.
Includes bibliographical references (pages 247-274) and index.
Keywords: Communities -- United States; United States -- Social conditions -- 21st century; United States -- Economic conditions -- 21st century; United States -- Civilization -- 21st century; Civilization; Communities; Economic history; Social conditions; United States; 2000-2099